Pictures versus words: can we use a pictorial scale to measure child health-related quality of life? - Tang, Tracy Chor Wai; Wong, Mun; Li, Jian-Bin; Chan, Derwin King Chung (Frontiers in Public Health, 2024)
Measuring health-related quality of life (HRQoL) is important because it can serve as an indicator or a predictor of subsequent mortality or morbidity. HRQoL has been shown to be directly related to child growth and development and indirectly related to the healthcare costs of young children. Existing measures of HRQoL in children have heavily relied on traditional questionnaires that use age-suited versions or parent proxy questionnaires. However, both of these methods may present with different types of biases and may misrepresent underlying HRQoL. The current mini reivew will first illustrate these methodological limitations and highlight the potential use of pictorial scales in addition to discussing their suitability for specifically measuring HRQoL as an alternative. We will also synthesize existing recommendations on the development of pictorial scales to provide a protocol as a recommendation to researchers who are aiming to develop an overall HRQoL pictorial scale that is suited for children.